2012
DOI: 10.4149/bll_2012_127
|View full text |Cite
|
Sign up to set email alerts
|

The effect of obstructive sleep apnea-hypopnea syndrome on acute myocardial infarction

et al.

Abstract: Background and objectives: Obstructive sleep apnea-hypopnea syndrome (OSAHS) is the most clinically common type of sleep-related breathing disorders. In this study, the effect of OSAHS on ST segment elevation myocardial infarction (STEMI) was investigated. Methods: Seventy-fi ve patients with STEMI were included in this study. The patients were divided into two groups: STEMI accompanied by OSAHS (O + ) group (33 patients) and STEMI without OSAHS (O -) group (42 patients). The differences of the clinical charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
1
7
0
1
Order By: Relevance
“…This data is in accordance with the proportion reported by previous studies [35, 36]. Our study showed that a greater BMI and abdominal circumference were associated with OSA ( P < 0.001, P = 0.046), since the BMI and abdominal obesity were reported as important factors in occurrence of OSA [3739].…”
Section: Discussionsupporting
confidence: 93%
“…This data is in accordance with the proportion reported by previous studies [35, 36]. Our study showed that a greater BMI and abdominal circumference were associated with OSA ( P < 0.001, P = 0.046), since the BMI and abdominal obesity were reported as important factors in occurrence of OSA [3739].…”
Section: Discussionsupporting
confidence: 93%
“…OSAS has been proposed as an independent risk factor for the development of essential hypertension and the isolated increase in diastolic pressure is often the earliest pressure modification in these subjects [24,37]. Some author have described higher incidence of myocardial infarction in OSAS subjects during night-time (from 10 pm to 6 am) [46] suggesting that OSAS could precipitate myocardial ischemia during sleep in patients with coronary disease. Untreated [24].…”
Section: Introductionmentioning
confidence: 99%
“…Some supported our result, such as Ludka's (10) research while the others had the opposite opinion, for example, Kuniyoshi et al (23) reported that there was a different diurnal variation among patients with AMI with or without SAHS. and Zhang et al (2) reported that myocardial infarction mainly occurred between 10 pm and 6 am among patients with OSAHS.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep apnoea hypopnoea syndrome (SAHS) causes repetitive nocturnal hypoxemia, which could promote the progression of hypertension, arrhythmia, coronary artery disease (CAD) and cerebral vascular disease (1,2). There are many reports regarding the effect of SAHS on high blood pressure (3,4) and arrhythmia (5,6).…”
Section: Introductionmentioning
confidence: 99%